Psychiatric disorders and characteristics of patients in_x000D_ asthmatic children and adolescents - (:unkn) unknown (My University, 2020)
Aim: The main objective of our study is to assess the socioeconomic, prenatal, neonatal and developmental properties of asthmacases who presented to child and adolescent psychiatry clinic and to compare psychiatric diagnosis frequency in terms of age andgender groups.Material and Methods: Patient files of 194 children and adolescents with asthma who admitted to our hospital child and adolescentpsychiatry outpatient clinic. were retrospectively reviewed. Patients' age, gender, parent education level and job status, mother'spregnancy history, delivery history, developmental stages and psychiatric diagnoses based on the Diagnostic and Statistical Manualof Mental Disorders- Fifth Edition (DSM-5) are noted.Results: Majority of parents of asthma patients had a primary school education and 21% of mothers were working full time. About14% of mothers reported smoking during pregnancy and 19% of children had delayed speech. In males and children with primaryschool age, attention-deficit hyperactivity disorder (ADHD) was frequent whereas female cases showed a higher rate of anxietydisorders.Conclusion: The prevalence of psychiatric disorders, especially ADHD and anxiety disorders, is high in children and adolescents withasthma. The presence of difficulties in terms of sociocultural, prenatal, neonatal and developmental characteristics may increase theneed to apply to the psychiatry outpatient clinics.